2009
DOI: 10.1038/nature07616
|View full text |Cite
|
Sign up to set email alerts
|

A tunable synthetic mammalian oscillator

Abstract: Autonomous and self-sustained oscillator circuits mediating the periodic induction of specific target genes are minimal genetic time-keeping devices found in the central and peripheral circadian clocks. They have attracted significant attention because of their intriguing dynamics and their importance in controlling critical repair, metabolic and signalling pathways. The precise molecular mechanism and expression dynamics of this mammalian circadian clock are still not fully understood. Here we describe a synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
436
2
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 539 publications
(444 citation statements)
references
References 28 publications
5
436
2
1
Order By: Relevance
“…On the contrary, negative autoregulation interactions are absent in robust topologies. Our result for positive autoregulation agrees with earlier studies which also demonstrated numerically (Tsai et al 2008) and experimentally Stricker et al 2008;Tigges et al 2009) the importance of positive autoregulation. In terms of having negative feedback loops in the network, at least one loop is required, with most robust topologies using at least two (Fig.…”
Section: Features Of Robust Oscillatory Topologiessupporting
confidence: 93%
See 1 more Smart Citation
“…On the contrary, negative autoregulation interactions are absent in robust topologies. Our result for positive autoregulation agrees with earlier studies which also demonstrated numerically (Tsai et al 2008) and experimentally Stricker et al 2008;Tigges et al 2009) the importance of positive autoregulation. In terms of having negative feedback loops in the network, at least one loop is required, with most robust topologies using at least two (Fig.…”
Section: Features Of Robust Oscillatory Topologiessupporting
confidence: 93%
“…4) or by inserting a third component in the positive branch of the feedback loop (Motifs 3, 4). Motif 1 is a well-known circuit, the ''amplified negative feedback oscillator'', where the key characteristic is to obtain significantly faster activator than repressor dynamics (Stricker et al 2008;Tigges et al 2009;Purcell et al 2010;Lomnitz and Savageau 2014). Motif 2, on the other hand, is less common in the literature, and it accounts more for not-so-robust topologies (median Oscillatory robustness is calculated as the fraction of parameter sets that yielded oscillatory responses parameters were randomly sampled 3 Â 10 5 times per topology.…”
Section: Motifs For Oscillatory Behaviormentioning
confidence: 99%
“…S1 and S2). The kinetic parameters were selected from literature (21,30). We performed sensitivity analysis of the output node Z protein concentration against the mRNA species of nodes X and Y (thereby emulating RNAi perturbation).…”
Section: Significancementioning
confidence: 99%
“…Le premier réseau de ce type, connu sous le nom de Répressilateur, formé par trois répresseurs organisés de manière cyclique, a été construit voici près de dix ans [42]. Depuis, d'autres réseaux génétiques oscillants ont été synthétisés [43][44][45]. À côté des travaux consacrés aux nombreux rythmes qui scandent la dynamique cellulaire, la biologie synthétique ouvre ainsi des voies prometteuses à la compréhension des rythmes du vivant.…”
Section: Nouveaux Rythmes Nouveaux Oscillateursunclassified